Towards A Phygital Church : Respons GKPB Fajar Pengharapan Bandung Terhadap Perkembangan Era Digital - Yessy Saputra (STT INTI Bandung, 2026)
Digital culture has permeated every aspect of human life, including the church. The phenomenon of digital churches had already emerged long before the COVID-19 pandemic and accelerated significantly during the pandemic period. Using a historical approach, this study found that GKPB Fajar Pengharapan has been highly progressive in adapting to the shifting trends of the era, including developments in communication technology. One of the key factors behind the progressiveness of GKPB Fajar Pengharapan lies in its leadership. Since the COVID-19 period, GKPB Fajar Pengharapan has gradually shifted from conventional communication technology to digital technology.